PROCESSOS MIDIATIVISTAS DE JORNALISMO AMBIENTAL: análise de cobertura jornalística da Amazônia Real - AMANDA FRANCO DE SOUZA (2022)
This dissertation aims to analyze the news coverage of Amazônia Real, an independent journalistic initiative born on the web, which focuses its agendas on environmental content, so that we can understand and configure a so-called mediativist environmental journalism. We start from the hypothesis that the narratives of these media take hold of Information and Communication Technologies (ICTs) for the production of activist tactics from different languages. Through a qualitative approach, the work is methodologically based on the adaptation of the protocol of Analysis of Journalistic Coverage (SILVA, MAIA, 2011) from three analytical levels: marks of investigation, marks of the composition of the product and socio-environmental contextual characterization, applied to eight reports of the Environment section of Amazônia Real, a space that we identified as the most similar to the characteristics of environmental journalism and mediativism through a survey conducted in the Map of Independent Journalism of Agência Pública. Above all, we evidence that although Amazônia Real reveals some proximities with the conventional media model in what concerns the format and the exploitation of sources, the analyzed reports point to a rupture in the journalistic content, since they go deeper into the issues and bring in their journalistic coverage most of the assumptions inherent to environmental journalism and mediativism, which leads us to conclude that this mediativist environmental journalism may be under construction.